GEOLOGICAL-GEOMORPHOLOGICAL PECULIARITIES OF THE BASIN OF THE MARMARIK RIVER: (right tributary of the Hrazdan River, Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Definite regularities have been revealed in the intensity of the dismemberment of the right-bank and left-bank slopes of the Marmarik River Valley by tributaries and ravines, in the ratio of the length and width of the basis of tributaries of the 2nd and 3rd order. The Marmarik River is one of the sixth order. The left tributaries have the most high orders. This ring of partition is explained by with the geological structure of the right-bank and left-bank slopes, the nature of their vegetation cover, as well as the steepness.
Keywords: Marmarik basin; tributaries; order of rivers; partition; blocks